EDUCATION OF SMART DEVICES ADDICTION IMPACT FOR ELEMENTARY SCHOOL STUDENTS DURING COVID-19 PANDEMIC - Esme Anggeriyane (UMBanjarmasin, 2022)
Since the implementation of restrictions on physical activity outside the home has an impact on the education sector. Children are required to study at home and the role of teachers must be largely replaced by parents. The difficulty of parents accompanying their children's activities causes parents to give gadgets to their children as a powerful solution for parents' assumptions. However, this is not entirely true because the use of gadgets that are not wise will cause children to become addicted to gadgets. The importance of health education about the impact of gadget addiction by targeting 13 students of class 1 can directly help to increase students' knowledge of using gadgets and can explore their curiosity directly by asking the educator team. The results showed that in the initial interview, most of the students had used gadgets and the results of the evaluation of the activities showed that the students could explain well the contents of the counseling material from the educator team. Increasing knowledge of children and their environment is very important to avoid deviations that can occur in children such as gadget addiction